Modified layered lithium-rich manganese-based positive electrode material as well as preparation method and application thereof

By nano-processing micron-level Li2MnO3 and mixing and modifying it with a strong oxidant, the problems of insufficient specific capacity, Coulombic efficiency, rate performance and cycle performance of Li2MnO3 in lithium-ion batteries have been solved, and the battery performance has been significantly improved.

CN119330405APending Publication Date: 2025-01-21CHANGDE COSPOWERS NEW ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411242662.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-05
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

Micron-level Li2MnO3 has problems with poor specific capacity performance, low Coulomb efficiency, poor rate performance and poor cycle performance for the first time.

Method used

Nanonization treatment is carried out through solution gel method, solution combustion method, solution self-propagation method, etc. to reduce the particle size of Li2MnO3, and the electrochemical properties of the material are improved by mixing with a strong oxidant.

Benefits of technology

Nanotechnology treatment improves the migration path of lithium ions, enhances the structural stability and electrochemical performance of the material, and significantly improves the first charge specific capacity and cycle performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330405A_ABST
    Figure CN119330405A_ABST
Patent Text Reader

Abstract

The invention discloses a modified layered lithium-rich manganese-based positive electrode material and a preparation method and application thereof, and belongs to the field of lithium battery positive electrodes. The method comprises the following steps: dissolving a lithium salt and a manganese salt in a solvent in proportion; adding a combustion improver into the mixed solution; putting the mixture into a high-temperature furnace for high-temperature calcination to form nanoscale Li2MnO3; the preparation method comprises the following steps: mixing nanoscale Li2MnO3 with a strong oxidant, so as to obtain modified nanoscale Li2MnO3; nanoscale Li2MnO3 is synthesized by using a solution gel method, a solution combustion method, a solution self-propagating method and the like. Under the nanoscale, the migration path of the lithium ions from the inside of the particles to the surface is greatly shortened, which means that the lithium ions can move in the electrode material more quickly, thereby accelerating the charging and discharging process of the battery. The high specific surface area of the nanoparticles provides more active sites, so that more lithium ions can be in contact with the surface of the material and participate in electrochemical reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of lithium battery positive electrodes, and specifically relates to a modified layered lithium-rich manganese-based positive electrode material and a preparation method and application thereof. Background Art

[0002] At present, the lithium battery market is booming at an astonishing rate, mainly due to the rapid rise of the electric vehicle and power storage markets. With the continuous expansion of these fields, the demand for lithium batteries is snowballing, and the requirements for battery performance are also rising, especially the expectations for battery capacity, which have reached an unprecedented height. As the main force of this energy revolution, lithium-ion batteries mainly include key components such as positive and negative electrodes, electrolytes, films, current collectors and shells. Among these many components, electrode materials play a vital role. It directly determines the capacity of the battery and is the key to improving battery performance. The optimization of positive and negative electrode materials can not only improve the energy density of the battery, but also extend the service life of the battery, which plays an immeasurable role in promoting the development of the lithium battery market.

[0003] In the current frontier exploration of lithium battery technology, the research and development of positive electrode materials is regarded as the key to improving battery performance. Among many materials, high-nickel ternary materials stand out with their mature technology and excellent energy density, but the Li / Ni mixing problem caused by their high nickel content poses a challenge to the cycle stability and safety of the battery, and has become a bottleneck that needs to be solved urgently. In contrast, lithium iron phosphate materials have won the favor of the market with their excellent cycle stability and safety, especially in application scenarios with strict requirements on safety performance. However, the limitations of its energy density and tap density, as well as its low ionic and electronic conductivity, limit its application in high-power demand scenarios, and the lack of rate performance has also become an obstacle to its further development.

[0004] In this context, manganese oxide cathode materials, especially layered lithium-rich manganese-based cathode materials xLi 2 MnO 3 ·(1-x)LiMO 2 (M=Mn, Ni, Co and other transition metal elements), has attracted much attention due to its unique performance advantages. This type of material can not only provide more than 250mAhg -1 The high specific capacity, excellent thermal stability and cost-effectiveness provide new possibilities for improving battery performance. 2 MnO 3 Each molecule contains two Li + , if two Li +After all of it is extracted, the specific capacity can reach 458mAh / g. Such a high specific capacity and the abundant manganese resources in nature make it worthy for researchers to explore using it alone as a positive electrode material for lithium-ion batteries.

[0005] However, existing micron-sized Li 2 MnO 3 There are disadvantages such as poor specific capacity, low initial Coulombic efficiency, poor rate performance, and poor cycle performance, because Li 2 MnO 3 Conduct research on particle size nano-sizing and modification. Summary of the invention

[0006] The purpose of this invention is to solve the problem of micron-scale Li 2 MnO 3 There are problems such as poor specific capacity performance, low first coulombic efficiency, poor rate performance, and poor cycle performance. A modified layered lithium-rich manganese-based positive electrode material and its preparation method and application are provided. This method converts the existing micron-sized Li 2 MnO 3 Nano-sizing is performed to reduce its particle size, and modification is performed on this basis to improve Li 2 MnO 3 electrochemical performance and cycle performance.

[0007] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0008] A method for preparing a modified layered lithium-rich manganese-based positive electrode material, the method comprising:

[0009] S1, dissolving lithium salt and manganese salt in a solvent in proportion;

[0010] S2, adding the combustion aid into the mixed solution obtained in S1;

[0011] S3, the mixture obtained in S2 is placed in a high temperature furnace and calcined at high temperature to form nano-scale Li 2 MnO 3 ;

[0012] S4, the nanoscale Li obtained in S3 2 MnO 3 Mixed with a strong oxidant to obtain modified nanoscale Li 2 MnO 3 .

[0013] Furthermore, the S2 also includes: drying the mixed solution containing the combustion aid to a gel state, and burning the gel to form a sponge-like fluffy oxide.

[0014] Furthermore, the drying process is to age at room temperature for 2 hours, and then dry at 120° C. to gel.

[0015] Furthermore, the combustion environment temperature is set to 120-220°C. When the environment temperature is 120-180°C, the gel is ignited at the center of the gel by burning igniters or strong lasers to form sponge-like fluffy oxides; when the environment temperature is 180-220°C, the gel spontaneously ignites at high temperature to form sponge-like fluffy oxides. The preferred ignition process is to use a strong laser to ignite the gel at the center of the gel at 140°C to form a sponge-like fluffy oxide.

[0016] Furthermore, in step S1, the lithium salt and manganese salt are nitrates, chlorides, carbonates, acetates whose metal ions are lithium and manganese, preferably nitrates; the solvent is water or liquid alcohol, preferably deionized water; the cation ratio of the lithium salt to the manganese salt is 1-4:1-4, preferably lithium ion: manganese ion = 2:1; the total cation concentration in the solution is 1.5 mol / L.

[0017] Furthermore, in step S2, the combustion improver is one or a combination of glycine, citric acid, urea, ethylene glycol, carboxyacetamide, hydrazine fuel, and glucose. Preferably, the combustion improver is one or a combination of glycine, citric acid, and ethylene glycol, and more preferably glycine. The amount of the combustion improver added is the total molar amount of the cationic charge number in the solution: the total molar amount of the combustion improver = 1:3-0.5. Preferably, the amount of the combustion improver added is the total molar amount of the cationic charge number: the total molar amount of the combustion improver = 1:1.5.

[0018] Furthermore, in step S3, the high temperature calcination temperature is 500-1000°C, preferably 600-800°C, the time is 4-24h, and preferably 12-16h.

[0019] Further, in step S4, the strong oxidant is one or more combinations of ammonium persulfate, hydrogen peroxide, potassium permanganate, sodium peroxide, perchlorate, persulfate, and nitric acid, preferably the strong oxidant is one or a combination of ammonium persulfate and potassium permanganate, more preferably, the strong oxidant is ammonium persulfate; in step S6, the nanoscale Li 2 MnO 3 The mass ratio of the strong oxidant to the strong oxidant is 1:1-0.1, preferably, the mass ratio is 1:0.4-0.2, and more preferably, the mass ratio is 1:0.3; the strong oxidant treatment time is 1-6H, and the preferred treatment time is 2H.

[0020] A modified layered lithium-rich manganese-based positive electrode material prepared by the above preparation method.

[0021] A modified layered lithium-rich manganese-based positive electrode material prepared by the above preparation method is used in lithium batteries.

[0022] The beneficial effects of the present invention compared with the prior art are as follows: the present invention uses a solution gel method, a solution combustion method, a solution self-propagation method, etc. to synthesize nano-scale Li 2 MnO 3 . At the nanoscale, the migration path of lithium ions from the inside of the particle to the surface is greatly shortened, which means that lithium ions can move faster in the electrode material, thereby accelerating the battery's charge and discharge process. The high specific surface area of ​​nanoparticles provides more active sites, allowing more lithium ions to contact the surface of the material and participate in electrochemical reactions. Nano-sizing can also improve the structural stability of the material, especially during cyclic charge and discharge. Smaller particle size helps to reduce the stress caused by the volume change of the material during charge and discharge, thereby reducing the possibility of structural damage and extending the life of the battery. By treating with strong oxidants, Li 2 MnO 3 The O ions in the material are reduced and detached from the crystal lattice to form oxygen vacancies, which can significantly improve the electrochemical properties of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 It is a process flow chart of the present invention. DETAILED DESCRIPTION

[0024] Those skilled in the art may refer to the contents of this article and make appropriate improvements to the process parameters as needed. It should be particularly noted that all similar replacements and modifications of the present application are obvious to those skilled in the art and are deemed to be included in the scope of the present application. The present application has described the products, processes and applications through the best embodiments, and relevant personnel may make appropriate changes, modifications and combinations without departing from the content, spirit and scope of the present application to implement and apply the technology of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without making creative work belong to the scope of protection of the present application.

[0025] It should be understood that, in this document, when terms such as "first", "second", "step 1", "step 2", "(1)", "(2)" and the like appear, they are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any actual relationship or order between them. In addition, the terms "include", "comprise" or any other variations thereof are intended to cover non-exclusive inclusion to include a process, method, article or device that includes a series of elements, including not only the elements that have been explicitly listed, but also other elements that are not listed, or elements that are inherent to the process, method, article or device. When the statement "includes one..." is used to limit an element, it does not exclude the possibility that there are other identical elements in the process, method, article or device that includes the element, unless otherwise limited. At the same time, the embodiments and features thereof in this application may be combined with each other without conflict.

[0026] Example 1

[0027] Reference Figure 1 , Figure 1 The preparation method of the modified layered lithium-rich manganese-based positive electrode material in this embodiment comprises the following steps:

[0028] S1: dissolving lithium nitrate and manganese nitrate in deionized water, wherein the molar ratio of lithium nitrate to manganese nitrate is lithium ion: manganese ion = 2:1, and the total cation concentration in the solution is 1.5 mol / L.

[0029] S2: Add glycine to the ionic solution obtained in S1, with the addition ratio being total cationic charge molar amount: glycine molar amount = 1:1.5.

[0030] S3: The ionic solution containing dissolved glycine is aged at room temperature 25° C. for 2 h, and then heated to 120° C. and dried to a gel state.

[0031] S4: Raise the temperature to 140°C and use a laser to ignite the center of the gel to form a sponge-like mixed oxide.

[0032] S5: High temperature calcination of sponge-like mixed oxides to produce nanoscale Li 2 MnO 3 , calcination temperature is 700℃, 12h.

[0033] S6: Nanoscale Li 2 MnO 3 Mixed with ammonium persulfate for modification, Li 2 MnO 3 The mass ratio with ammonium persulfate is 1:0.3, and the treatment time is 2 hours.

[0034] Example 2

[0035] S1: dissolving lithium nitrate and manganese nitrate in deionized water, wherein the molar ratio of lithium nitrate to manganese nitrate is lithium ion: manganese ion = 2:1, and the total cation concentration in the solution is 1.5 mol / L.

[0036] S2: Add citric acid to the ionic solution obtained in S1, with the addition ratio being total cationic charge molar amount: citric acid molar amount = 1:1.5.

[0037] S3: The ionic solution containing citric acid is aged at room temperature 25° C. for 2 h, and then heated to 120° C. and dried to a gel state.

[0038] S4: Raise the temperature to 140°C and use a laser to ignite the center of the gel to form a sponge-like mixed oxide.

[0039] S5: High temperature calcination of sponge-like mixed oxides to produce nanoscale Li 2 MnO 3 , calcination temperature is 700℃, 12h.

[0040] S6: Nanoscale Li 2 MnO 3 Mixed with ammonium persulfate for modification, Li 2 MnO 3 The mass ratio with ammonium persulfate is 1:0.3, and the treatment time is 2 hours.

[0041] Example 3

[0042] S1: dissolving lithium nitrate and manganese nitrate in deionized water, wherein the molar ratio of lithium nitrate to manganese nitrate is lithium ion: manganese ion = 2:1, and the total cation concentration in the solution is 1.5 mol / L.

[0043] S2: Add ethylene glycol to the ionic solution obtained in S1, with the addition ratio being total cationic charge molar amount: ethylene glycol molar amount = 1:1.5.

[0044] S3: The ionic solution containing ethylene glycol was placed in a muffle furnace and calcined at 700 °C for 12 h to produce nanoscale Li 2 MnO 3 .

[0045] S4: Nanoscale Li 2 MnO 3 Mixed with ammonium persulfate for modification, Li 2 MnO 3 The mass ratio with ammonium persulfate is 1:0.3, and the treatment time is 2 hours.

[0046] Example 4

[0047] S1: lithium acetate and manganese acetate are dissolved in deionized water, the molar ratio of lithium acetate to manganese acetate is lithium ion: manganese ion = 2:1, and the total cation concentration in the solution is 1.5 mol / L.

[0048] S2: Add glycine to the ionic solution obtained in S1, with the addition ratio being total cationic charge molar amount: glycine molar amount = 1:1.5.

[0049] S3: The ionic solution containing glycine was placed in a muffle furnace and calcined at 700 °C for 12 h to produce nanoscale Li 2 MnO 3 .

[0050] S4: Nanoscale Li 2 MnO 3 Mixed with ammonium persulfate for modification, Li 2 MnO 3 The mass ratio with ammonium persulfate is 1:0.3, and the treatment time is 2 hours.

[0051] Example 5

[0052] The difference from Example 1 is that potassium permanganate is selected as the strong oxidant in S6.

[0053] Example 6

[0054] The difference from Example 1 is that: Li in S6 2 MnO 3 The mass ratio of ammonium persulfate to sodium persulfate is 1:0.4.

[0055] Example 7

[0056] The difference from Example 1 is that: Li in S6 2 MnO 3 The mass ratio of ammonium persulfate to sodium persulfate is 1:0.2.

[0057] Comparative Example 1

[0058] The difference from Example 1 is that the modification treatment in S6 is not performed.

[0059] Comparative Example 2

[0060] S1: Lithium carbonate and manganese carbonate in molar amounts of Li 2 CO 3 :MnO 2 =1:1 and mix evenly by high-speed ball milling. Lithium needs to be in excess of 1% to make up for the lithium ions lost during the calcination process.

[0061] S2: The mixed powder obtained in S1 is calcined at 600°C for 24 hours.

[0062] S3: Li obtained in S2 2 MnO 3 Mixed with ammonium persulfate for modification, Li 2 MnO 3 The mass ratio with ammonium persulfate is 1:0.3, and the treatment time is 2 hours.

[0063] Comparative Example 3

[0064] The difference from Comparative Example 2 is that the modification treatment in S3 is not performed.

[0065] The layered Li prepared in Examples 1-7 and Comparative Examples 1-3 2 MnO 3 The sample was used as the positive electrode active material. The positive electrode active material: conductive agent (SP): binder (PVDF) = 90:5:5 was made into a positive electrode slurry according to the mass ratio and then coated on the positive electrode collector to form a positive electrode. The lithium sheet was used as the negative electrode. A conventional rate-type electrolyte was selected. The button battery was assembled and the battery performance tester was used to test the battery performance at 25°C in the test cabinet. The charge and discharge cut-off voltage was 2.0-4.75V, the charge and discharge rate was 0.2C, and the cycle was 50 weeks. The electrical performance test results are shown in Table 1.

[0066] Table 1 Electrical performance test results of products obtained from Examples 1-7 and Comparative Examples 1-3

[0067]

[0068] From the comparison of Examples 1, 6, and 7 with Comparative Example 1 in Table 1, it can be seen that as the degree of oxidation of the material increases, the specific capacity of the first charge shows a downward trend. This phenomenon is due to the early release of lithium ions under the action of strong oxidants - the increase in the content of oxidants is directly related to the pre-release of more lithium ions. At the same time, the amount of oxygen vacancies generated increases accordingly, which is Li 2 MnO 3 Lithium ions are released more easily during the charge and discharge cycle, thereby improving the initial efficiency.

[0069] It is worth noting that when Li 2 MnO 3 When the ratio with strong oxidant exceeds 1:0.3, the first efficiency jumps to more than 100%. This phenomenon can be attributed to the increase of oxygen vacancies, which increases the role of Mn ions as redox centers in the lithium deintercalation process, thereby allowing more active Mn ions to participate in the reaction, contributing significantly to the capacity improvement.

[0070] Comparing Example 1 with Comparative Examples 1 and 3, Li prepared by liquid phase method 2 MnO 3It shows a higher first charge specific capacity. This is due to the smaller particle size of the material prepared by the liquid phase method. The smaller particle size shortens the diffusion path of lithium ions and reduces the polarization resistance, thereby optimizing the electrochemical performance.

[0071] In summary, through process improvement and material modification, the present invention has explored a practical path for the application of layered lithium-rich manganese-based materials in the field of lithium-ion battery positive electrodes, and provided a new idea for improving battery performance. This scheme not only optimizes the initial efficiency of the material, but also achieves a significant improvement in performance by regulating the material structure, contributing to the innovation of battery technology. The above is only an embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various changes and variations. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of the claims of the present invention.

Claims

1. A method for preparing a modified layered lithium-rich manganese-based positive electrode material, characterized in that: The method is: S1, dissolving lithium salt and manganese salt in a solvent in proportion; S2, adding the combustion aid into the mixed solution obtained in S1; S3, calcining the mixture obtained in S2 at high temperature to form nano-sized Li2MnO3; S4. Mix the nano-sized Li2MnO3 obtained in S3 with a strong oxidant to obtain modified nano-sized Li2MnO3.

2. The method for preparing a modified layered lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: The step S2 further includes: drying the mixed solution containing the combustion aid to a gel state, and burning the gel to form a sponge-like fluffy oxide.

3. The method for preparing a modified layered lithium-rich manganese-based positive electrode material according to claim 2, characterized in that: The drying process is to age at room temperature for 2 hours, and then dry at 120°C until it gels.

4. The method for preparing a modified layered lithium-rich manganese-based positive electrode material according to claim 2, characterized in that: The ambient temperature of the combustion is set at 120-220°C.

5. A method for preparing a modified layered lithium-rich manganese-based positive electrode material according to any one of claims 1 to 4, characterized in that: In step S1, the lithium salt and manganese salt are nitrates, chlorides, carbonates and acetates of lithium and manganese metal ions; the solvent is water or liquid alcohol; the cation ratio of the lithium salt to the manganese salt is 1-4:1-4; and the total cation concentration in the solution is 1.5 mol / L.

6. A method for preparing a modified layered lithium-rich manganese-based positive electrode material according to any one of claims 1 to 4, characterized in that: In step S2, the combustion improver is one or a combination of glycine, citric acid, urea, ethylene glycol, carboxyacetamide, hydrazine fuel, and glucose; the added amount of the combustion improver is the total molar amount of the cationic charge number in the solution: the total molar amount of the combustion improver = 1:3-0.

5.

7. A method for preparing a modified layered lithium-rich manganese-based positive electrode material according to any one of claims 1 to 4, characterized in that: In step S3, the high temperature calcination is carried out at a temperature of 500-1000° C. and for a time of 4-24 hours.

8. A method for preparing a modified layered lithium-rich manganese-based positive electrode material according to any one of claims 1 to 4, characterized in that: In step S4, the strong oxidant is one or more combinations of ammonium persulfate, hydrogen peroxide, potassium permanganate, sodium peroxide, perchlorate, persulfate, and nitric acid; in step S6, the mass ratio of the nano-scale Li2MnO3 to the strong oxidant is 1:1-0.1; and the strong oxidant treatment time is 1-6 hours.

9. A modified layered lithium-rich manganese-based positive electrode material prepared by the preparation method according to any one of claims 1 to 8.

10. A modified layered lithium-rich manganese-based positive electrode material prepared by the preparation method according to any one of claims 1 to 8 for use in a lithium battery.